2009
DOI: 10.1097/cad.0b013e3283262a32
|View full text |Cite
|
Sign up to set email alerts
|

Acquired vorinostat resistance shows partial cross-resistance to ‘second-generation’ HDAC inhibitors and correlates with loss of histone acetylation and apoptosis but not with altered HDAC and HAT activities

Abstract: Histone deacetylase (HDAC) inhibitors such as vorinostat (suberoylanilide hydroxamic acid), valproic acid, romidepsin , and LBH589 comprise a relatively new class of potent anticancer agents. This study provides evidence for the potential of vorinostat to cause acquisition of multidrug resistance protein-independent resistance in HCT116 colon tumor cells. This acquired resistance is moderate (two-fold to three-fold), is nonreversible, and correlates with the loss of responses typically seen with HDAC inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…The molecular mechanism for acquired resistance varies in different HDACi-resistant cells. The acquired resistance of HCT116/VOR cells was associated with a reduction in histone acetylation, G2/M checkpoint activation and apoptosis susceptibility (20). Pan-HDACi-resistant HL-60/LR cells expressed higher levels of HDAC1, 2 and 4, but lacked expression of HDAC6, with concomitant hyper-acetylation of heat shock protein 90 (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The molecular mechanism for acquired resistance varies in different HDACi-resistant cells. The acquired resistance of HCT116/VOR cells was associated with a reduction in histone acetylation, G2/M checkpoint activation and apoptosis susceptibility (20). Pan-HDACi-resistant HL-60/LR cells expressed higher levels of HDAC1, 2 and 4, but lacked expression of HDAC6, with concomitant hyper-acetylation of heat shock protein 90 (21).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that HL-60/LR cells, human acute myeloid leukemia cells resistant to LAQ824 (a hydroxamic acid analog pan-HDACi), exhibited a markedly higher growth compared with parental HL-60 cells (21). A vorinostat-induced subline, HCT116/vorinostat, exhibited a slightly slower growth rate compared with the parental HCT116 cell line (20). The different results indicate that the growth rate of HDACi-resistant cell lines may be drug-specific, cell type-specific or even case-specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that suberoylanilide hydroxamic acid (SAHA, vorinostat), a representative of the class of histone deacetylase (HDAC) inhibitors, can cause acquisition of irreversible and multidrug resistance-independent HDAC inhibitor-resistance in HCT116 colon tumor cells, with the corresponding losses of growth inhibition, of apoptosis, and of histone acetylation (1,2). HDAC inhibitors are a class of anticancer agents that act by epigenetically regulating gene expression through chromatin remodeling.…”
Section: Introductionmentioning
confidence: 99%